TATA KELOLA PEMERINTAHAN DALAM PROGRAM PILAH SAMPAH DI KOTA SEMARANG - Jennifer Evelyn Sartika Silalahi; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The increasing volume of urban solid waste has become a major environmental challenge in Semarang City, particularly regarding the burden of waste disposed at the Jatibarang Landfill, prompting the Semarang City Government to implement the Waste Sorting Program as a reduction strategy. This study aims to analyze the governance of that program using a good governance framework with indicators of transparency, accountability, effectiveness and efficiency, and public participation, further enriched by the integration of the Integrated Sustainable Waste Management (ISWM) framework encompassing three dimensions, namely physical system elements, stakeholder involvement, and sustainability aspects, to enable a more contextual analysis of urban solid waste management. This research employed a qualitative approach with a case study method. Primary data were collected through in-depth interviews with the Semarang City Environmental Agency, village heads in five urban villages, and community members of urban villages. Secondary data were obtained from waste management statistics and program documentation. The findings indicate that the governance of the Waste Sorting Program in Semarang City has reflected the application of good governance principles, particularly in information dissemination, community involvement in implementation, and the utilization of various resources. However, several limitations remain, including insufficient transparency of program performance data, an unintegrated reporting system, and the lack of significant reduction in waste volume delivered to the landfill. Community participation also varies across areas. Based on these findings, this study recommends improving data transparency and regular publication of program performance, strengthening integrated reporting systems, intensifying community assistance at the local level, and developing sustainable strategies through multi-stakeholder collaboration.